2013
DOI: 10.1016/j.stem.2013.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming Fibroblasts into Bipotential Hepatic Stem Cells by Defined Factors

Abstract: Recent studies have demonstrated direct reprogramming of fibroblasts into a range of somatic cell types, but to date stem or progenitor cells have only been reprogrammed for the blood and neuronal lineages. We previously reported generation of induced hepatocyte-like (iHep) cells by transduction of Gata4, Hnf1α, and Foxa3 in p19 Arf null mouse embryonic fibroblasts (MEFs). Here, we show that Hnf1β and Foxa3, liver organogenesis transcription factors, are sufficient to reprogram MEFs into induced hepatic stem c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
150
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(160 citation statements)
references
References 49 publications
9
150
0
1
Order By: Relevance
“…The successfully generated iHEP cells from mouse by two separate groups were validated by expressional analysis [37,76]. Induced hepatic stem cells (iHepSCs), which possess the potential to differentiate into both hepatocytic and cholangiocytic cells, were characterized and their potential confirmed by global expression analysis [104]. Again, when a human iHEP reprogramming protocol was published, expressional analysis confirmed hepatocyte gene network activation [24,38].…”
Section: Induced Hepatocytesmentioning
confidence: 90%
“…The successfully generated iHEP cells from mouse by two separate groups were validated by expressional analysis [37,76]. Induced hepatic stem cells (iHepSCs), which possess the potential to differentiate into both hepatocytic and cholangiocytic cells, were characterized and their potential confirmed by global expression analysis [104]. Again, when a human iHEP reprogramming protocol was published, expressional analysis confirmed hepatocyte gene network activation [24,38].…”
Section: Induced Hepatocytesmentioning
confidence: 90%
“…In the same time, Chinese research teams 9 reported in independently that new cocktails of transcription factors of Gata4, HNF1alpha, Foxa3, and RNAi-mediated inactivation of p19Arf for direct induction of functional hepatocyte like from mouse tail-tip fibroblasts. Yu et al, 10 brilliantly decided to explore two liver organogenesis transcription factors Hnf1b and Foxa3, to reprogram mouse embryonic fibroblasts into induced hepatic stem cells and successfully converted to induced hepatic stem cells from mouse embryonic fibroblasts. They proved that these induced Figure 1 (a) Conventional route reprogramming methods for pluripotent state and thereafter hepatic differentiation, (b) Shortcut route reprogramming methods for endodermal state and thereafter hepatic differentiation, (c) Hypothetical future shortest route for liver regeneration of acute and chronic liver by local delivery of hepatic endodermal and liver organogenesis transcription factors.…”
Section: Commentsmentioning
confidence: 99%
“…Recently, researchers used such liver specific transcription factors for generation of hepatocyte cells from skin fibroblast cells in vitro. [8][9][10][11][12] The ultimate aim of generation of hepatocytes from skin cells to treat liver diseases. If we know the transcription factors and small molecules which have potential to convert hepatocyte from fibroblast, why not to explore transcription factors and small molecules in vivo directly to repair or regenerating the tissue or organs.…”
Section: Commentsmentioning
confidence: 99%
“…In the past, the use of NSCs for the treatment of neurological disease was hindered by limited fetal and adult NSC sources. Recent advances in cellular reprogramming allowed for the generation of induced pluripotent stem cells (iPS) and somatic stem cells from various somatic tissues [2][3][4][5][6]. To that effect, NSCs can be obtained by differentiation from iPS cells [7,8].…”
Section: Introductionmentioning
confidence: 99%